2022
DOI: 10.1186/s13690-022-00844-z
|View full text |Cite
|
Sign up to set email alerts
|

The InfAct proposal for a sustainable European health information infrastructure on population health: the Distributed Infrastructure on Population Health (DIPoH)

Abstract: Background In Europe, data on population health is fragmented, difficult to access, project-based and prone to health information inequalities in terms of availability, accessibility and especially in quality between and within countries. This situation is further exacerbated and exposed by the recent COVID-19 pandemic. The Joint Action on Health Information (InfAct) that builds on previous works of the BRIDGE Health project, carried out collaborative action to set up a sustainable infrastructu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…The status of availability of health information, including health and healthcare service-related data, research networks 7 and projects, health reporting 13 and capacity-building activities 14 in Europe was reviewed. The review demonstrated severe and worrisome fragmentation of the information resulting in the recommendation to establish a European health information infrastructure 15 where the HIP would be one of the key pillars provided to strengthen evidence-informed policymaking and research. Other pillars were training and capacity building and direct exchange of expertise and good practices.…”
Section: Methodsmentioning
confidence: 99%
“…The status of availability of health information, including health and healthcare service-related data, research networks 7 and projects, health reporting 13 and capacity-building activities 14 in Europe was reviewed. The review demonstrated severe and worrisome fragmentation of the information resulting in the recommendation to establish a European health information infrastructure 15 where the HIP would be one of the key pillars provided to strengthen evidence-informed policymaking and research. Other pillars were training and capacity building and direct exchange of expertise and good practices.…”
Section: Methodsmentioning
confidence: 99%
“…The PHIRI project brings together 41 partners in 30 different countries with the aim of sharing data and expertise on the COVID-19 pandemic through a health Information portal on population health and a broader goal of constructing sustainable and reactive health information systems in Europe and promoting their use for policy decisions 13 . A key component of the project is to conduct research to inform public health policies and management of the COVID-19 pandemic using a federated data model with four use cases, including one on perinatal health and perinatal health inequalities.…”
Section: Methodsmentioning
confidence: 99%
“…2 Following the results of BRIDGE Health, the Joint Action on Health Information (JA InfAct) identified the necessity to create a new Distributed Research Infrastructure on Population Health and a comprehensive training program for scientific and administrative staff to improve the availability of comparable, robust and policy-relevant data, and information on health system performance. 3 Continuing to boost these recommendations, the ‘Population Health Information Research Infrastructure’ (PHIRI) was developed to facilitate and generate the best available evidence for research on the health and well-being of populations impacted by COVID-19. 4 , 5 PHIRI involves national public health institutes, research centres, universities, and ministries of health, fostering collaboration between different perspectives and expertise.…”
Section: Introductionmentioning
confidence: 99%